2020
DOI: 10.2147/cmar.s267844
|View full text |Cite
|
Sign up to set email alerts
|

<p>Long Non-Coding RNA <em>PITPNA-AS1</em> Accelerates the Progression of Colorectal Cancer Through <em>miR-129-5p</em>/<em>HMGB1</em> Axis</p>

Abstract: Background: Long non-coding RNAs (lncRNAs) are essential regulators in colorectal cancer (CRC) progression. This work aimed to delve into the characteristics of lncRNA PITPNA-AS1 in CRC. Methods: Quantitative real-time polymerase chain reaction (qRT-PCR) was adopted to examine PITPNA-AS1, miR-129-5p, high-mobility group box-1 (HMGB1) mRNA expressions in CRC tissues and cell lines. Functionally, cell counting kit-8 (CCK-8) and 5-ethynyl-2-deoxyuridine (EdU) incorporation assays were employed to examine cell pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 21 publications
(30 reference statements)
2
10
0
Order By: Relevance
“…Our functional analyses demonstrate that miR-129-5p inhibits cell proliferation, cell cycle progression and that it mediates BRAFi response in BRAF mutated melanoma. This is in line with previous in vitro studies reporting that miR-129-5p acts as tumor suppressor in lung cancer [65], gastrointestinal cancer [55,57,66,67], esophageal squamous cell carcinoma [68,69], hepatocellular cancer [70], cervical cancer [71], breast cancer [43,72], and glioblastoma [73].…”
Section: Discussionsupporting
confidence: 91%
“…Our functional analyses demonstrate that miR-129-5p inhibits cell proliferation, cell cycle progression and that it mediates BRAFi response in BRAF mutated melanoma. This is in line with previous in vitro studies reporting that miR-129-5p acts as tumor suppressor in lung cancer [65], gastrointestinal cancer [55,57,66,67], esophageal squamous cell carcinoma [68,69], hepatocellular cancer [70], cervical cancer [71], breast cancer [43,72], and glioblastoma [73].…”
Section: Discussionsupporting
confidence: 91%
“…Previously, the prognostic value of PITPNA-AS1 was also reported in colorectal cancer and cervical cancer (12,15). Our study firstly provided clinical evidence that PITPNA-AS1 may be used as a novel biomarker.…”
Section: Discussionsupporting
confidence: 62%
“…We also observed that patients with high PITPNA-AS1 expression exhibited advanced clinical stages, positive metastasis and poor prognosis than those with low PITPNA-AS1 expression. Previously, the prognostic value of PITPNA-AS1 was also reported in colorectal cancer and cervical cancer ( 12 , 15 ). Our study firstly provided clinical evidence that PITPNA-AS1 may be used as a novel biomarker.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations